Recent Referees (Journal of Political Economy, 2018)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Brant AbbottRan AbramitzkyRodrigo AdaoNikhil AgarwalTreb AllenDouglas AlmondIsaiah AndrewsPeter ArcidiaconoEnghin AtalayAdrien AuclertNed AugenblickEduardo AzevedoLinda BabcockMarco BattagliniVivek BhattacharyaSourav BhattacharyaAlberto BisinDan BlackHenning BohnLaurent BoutonBen BrooksMarshall BurkeLeonardo BursztynSteven CallanderNicolas Castro CienfuegosDavid CesariniPierre-Andre ChiapporiEugene ChooGregory ClarkJohn CochraneDean CorbaeThomas CovertJacques CraemerErnesto Dal BoBrendan DaleyLucas DavisDamien De WalqueMark DeanManasi DeshpandeDouglas DiamondRebecca DiamondMichael DinersteinJonathan DingelJeremiah DittmarWill DobbieDave DonaldsonUlrich DoraszelskiPierre DuboisGeorgy EgorovAlon EizenbergBenjamin EnkeDennis EppleChristine ExleyPablo FajgelbaumArmin FalkRobert FeenstraAmy FinkelsteinRaymond FismanMarco FrancesconiBrigham FrandsenEric FrenchChao FuDrew FudenbergThomas FujiwaraManolis GalenianosCecile GaubertAndrew Goodman-BaconDavid GreenMatthew GrennanAdam GurenRong HaiJessie HandburyEric HanushekBard HarstadTarek HassanNathaniel HendrenRichard HoldenElisabeth HonkaMatteo IacovielloMurat IyigunKelsey JackSaumitra JhaCharles JonesDamon JonesJohn KennanPhilipp KircherNobuhiro KiyotakiPatrick KlineNarayana KocherlakotaRachel KrantonIlan KremerVijay KrishnaZoe KuehnEliana La FerraraNicola LaceteraDavid LagakosRicardo LagosRasmus LandersoeVictor LavyRobin LeeTracy LewisHaizhen LinMatthew LindquistBarton LipmanCorinne LowFernando LucoLilia MaliarDavid MalisonGustavo MansoErin MansurGiovanni MastrobuoniBhashkar MazumderMaurizio MazzoccoDavid McKenzieBruce MeyerVirgiliu MidriganEdward MiguelAhmed MobarakJoao MontezMelanie MortenCharles MurryCaitlin MyersDerek NealDavid NeumarkVolker NockeMasao OgakiPaulina OlivaPaul OyerBerk OzlerYoungmin ParkMario PascoaEduardo Perez-RichetRicardo Perez-TrugliaWolfgang PesendorferJose-Luis PeydroMassimiliano PisaniTomasz PiskorskiDevin PopeDrazen PrelecDavid RahmanSharon RameySteven RaphaelMartin RavallionAlex Rees-JonesM. RehaviPhilip RenyJose Rios-RullJames RobertsAriel RubinsteinThomas RuchtiMarc RysmanLawrence SchmidtMehdi ShadmehrJacob ShapiroRon SiegelEric SimsHoward SmithPaulo SomainiDavid StrombergChris SwannYuya TakahashiDmitry TaubinskyFelix TintelnotPetra ToddAlexander TorgovitskyRobert TownsendJuuso ValimakiStijn Van NieuwerburghJoseph VavraGreg VeramendiLise VesterlundAnnette Vissing-JorgensenAlessandra VoenaNico VoigtlaenderJessica WachterChristopher WaltersRoberto WeberBirger WernerfeltAsher WolinskyAlexander WolitzkyPierre YaredNese YildizAli YurukogluBasit ZafarJidong ZhouOwen ZidarSarah ZubairyGabriel Zucman Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 126, Number 5October 2018 Article DOIhttps://doi.org/10.1086/700865 © 2018 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.